Electronic characteristics of self-assembled hybrid devices based on PPV and CdS nanoparticles - Cho, J; Char, K; Hong, JD; Kim, D (GORDON BREACH SCI PUBL LTD, 2000)
Electronic characteristics of organic/inorganic hybrid devices based on CdS nanoparticle, poly(p-phenylene vinylene) (PPV) and poly(sodium styrene sulfonate) (PSS) were investigated. The average diameter of anionic CdS nanoparticles was measured to be 1 nm as judged from TEM and optical spectral characterization. The Quantum efficiency of the ITO/(PPV/PSS)(15)(PPV/CdS)(5)/Al device was significantly improved in comparison with that of the ITO/(PPV/PSS)(20)/Al device, The performance improvement of the ITO/(PPV/FSS)(15)(PrV/CdS)(5)/Al device is believed to be due to the low energy barrier of CdS nanoparticles for the electron injection from Al electrode.
Keywords: ELECTROLUMINESCENCE; POLYMER